Advances in the discovery of exosome inhibitors in cancer. (1st January 2020) - Zhang, Huarui; Lu, Jun; Liu, Jin; Zhang, Ge; Lu, Aiping
Abstract: Exosomes are small membrane vesicles released by most eukaryotic cells. They are considered to play an essential role in cell-to-cell communication, and It is also found that they serve as functional mediators in many severe diseases, including progression of various types of cancers. Inhibition of exosome release may slow the progression of some cancers; thus, exosome has been an attractive target for cancer treatment. Over the years, considerable efforts have been made to discover novel, highly potent and excellently selective exosome inhibitors. Most of these inhibitors are derived from synthetic compounds, some of which are currently existed drugs and found to have the potential to inhibit exosome release. In this review, we briefly discussed the development of exosome inhibitors that are currently discovered and provided guidance for the future development of inhibitors.